SPE Eastern Regional Meeting 2021
DOI: 10.2118/201787-ms
|View full text |Cite
|
Sign up to set email alerts
|

Review of Friction Reducers Performance Applied to the Marcellus Shale Region

Abstract: Polyacrylamide-based friction reducers (FRs) are widely used in hydraulic fracturing to reduce friction created within fluid as it flows through tubulars or other restrictions. These polymers generally add viscosity to the fluid to reduce the turbulence induced as fluid flows. Type and amount of total dissolved solids (TDS) in source water have significant impact on performance of FRs. This study investigates these effects and evaluates various types of FRs applied to the Marcellus Shale region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…81,82 However, even in the presence of a small amount of salt, the performance of HVFR fluids will sharply decrease. 13,83 FRs are the most commonly used type. Compared to anions, the cationic FRs are more salt-resistant.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
See 3 more Smart Citations
“…81,82 However, even in the presence of a small amount of salt, the performance of HVFR fluids will sharply decrease. 13,83 FRs are the most commonly used type. Compared to anions, the cationic FRs are more salt-resistant.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…Free radical coupling may also occur, which may increase molecular weight and thus increase the likelihood of formation damage. 83 Abaa et al 90 reported that the FRs intrude into the matrix of rock samples, which may block the rock pores. The laboratory research has confirmed that the retained conductivity of the proppant pack through which the FRs flowed was approximately 80%.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
See 2 more Smart Citations